Synthesis of Hydrochar Cassava peels with hydrothermal carbonization method and applications as hard water softener - Dzikria Sari Pratiwi; Wirda Udaibah; Kustomo Kustomo (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2021)
Groundwater before being used is very important to pay attention to the quality of the water. Water has good quality if it is in accordance with several parameters, including chemical, physical, and biological parameters. Mineral salt content is one of the chemical parameters that can be used to determine the quality of water. In this study, the synthesis of cassava peel hydrochar was successfully carried out using the hydrothermal carbonization (HTC) method. This material was developed to reduce waste of cassava peel biomass and overcome the problem of water hardness. HTC cassava peel was developed as an alternative hard water softener adsorbent. The results of FTIR characterization on hydro-activation (activating hydrochar) and hydro-non (non-activating hydrochar) contain functional groups of O-H stretch, C-H stretch, C≡C stretch and C=C stretch. Observation of surface morphology by SEM method on hydro-non in the form of large sheets, while the surface on hydro-activities in the form of small sheets. The adsorption capacity of hydro-active against Ca2+ ions and Mg2+ ions were 85.240 mg/g and 87.210 mg/g, respectively. Meanwhile, the hydro-non adsorption capacity of Ca2+ and Mg2+ ions were 84,736 mg/g and 85,713 mg/g. The kinetics of hydro-active adsorption on Mg2+ ion took place on order 3 (0.000003 min-1) while when adsorption of Ca2+ ion took place on order 0 (0.0324 min-1).©2021 JNSMR UIN Walisongo. All rights reserved.